Medical Management Guidelines for the Provision of Dental Care - Michael Siegel (Association of American Medical Colleges, 2012)
Abstract The purpose of this module is to assist health care professionals (dental, medical, nursing, pharmacy, and allied) in recognizing commonly occurring medical considerations that frequently arise in the provision of dental care. The intended outcome of this guide is to provide oral health and access to care for the patients entrusted to our care. This necessitates that the health care professionals work together in an effort to exchange their expertise so as to maximize the dental and medical prognosis for the patient. This guide is not intended as a definitive text on the diagnosis and management of oral and maxillofacial pathology, nor is it a treatise on internal medicine. This guide includes the most commonly encountered medical issues that arise in the routine provision of dental care. The literature cited is current at the time of publication; the user of this guide should ensure that the literature utilized in their clinical decision making is current. Both medical and dental educators can utilize this guide as a template for modifying their curricula. The initial iteration of this guide has been made available to all dental students and specialty residents in the classroom and is directly accessible in Nova Southeastern University's patient care electronic record (AxiUm). Users reference this guide in order to assess the patient in light of current medical guidelines that might alter the dental treatment plan. This guide is then used as the basis for the structuring of a medical consultation to the patient's primary care provider. Faculty have used this guide in ordering laboratory testing, consulting with the primary medical provider, in patient evaluation, and in constructing lectures.